Моделирование роста кольцевой трещины в цилиндрическом элементе конструкции при циклическом нагружении - Гонтаровский, Павел Петрович; Шульженко, Николай Григорьевич; Гармаш, Наталия Григорьевна; Мележик, Ирина Ивановна (НТУ "ХПИ", 2018)
Рассматривается кинетика кольцевой трещины в цилиндре с разными уровнями циклического нагружения. Применяется предложенная ранее методика расчетной оценки развития трещин в пластинчатых и осесимметричных конструкциях при циклическом нагружении, которая основана на концепции накопления рассеянных повреждений в материале. Упруго-пластическое деформирование материала в районе трещины определяется с помощью метода конечных элементов, а повреждаемость оценивается с использованием диаграмм усталостного разрушения гладких цилиндрических образцов. Учитывается контакт берегов трещины при сжимающих нагрузках. Результаты согласуются с данными, полученными по методу Ньюмана. Предлагаемая методика может быть использована для оценки живучести элементов паровых турбин (тепловых канавок роторов на пуско-остановочных режимах, замковых соединений лопаток с дисками и др.).

The purpose of these studies was to work out the methods for the computation of crack development in the plate and axisymmetric elements of structures at cyclic loading for the plasto-elastic arrangement using the conception of the accumulation of scattered damages in the material. In the domain in question, we simulated the processes of alternating-sign plasto-elastic deformation and the material crack resistance was estimated using the fatigue test data for smooth specimens. Thermal and elastically-deformed states of the structure were determined for different loading modes using the finite elements method. The material damageability was assessed for the curves of low-cycle fatigue and for the range of plasto-elastic deformations on the route of probable crack propagation using the hypothesis of linear summation. As soon as a critical value of the damageability is achieved the crack is propagated stepwise for the specified step. As an example, consideration was given to the kinetics of circumferential crack in the cylindrical element exposed to the axial-symmetric cyclic loading. The contact of crack edges was taken into consideration for compressing loading semicycles. The obtained data agree with the data obtained using the Newman method. The suggested technique can be used for the estimation of survivability of the elements of steam turbines (heat rotor grooves at start-up-stop modes, blade and disk interlocks, etc.).
Simulation of the propagation of circumferential crack in the cylindrical element structure exposed to cyclic loadings
Keywords: кинетика трещины; циклическая нагрузка; упруго-пластические деформации; размахи; малоцикловая усталость; кривые; метод конечных элементов; коэффициент асимметрии цикла; контакт берегов трещины; crack kinetics; cyclic loading; plasto-elastic deformation range; low-cycle fatigue curves; finite elements method; cycle asymmetry factor; contact of crack edges